If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12x+3=-5x+10
We move all terms to the left:
12x+3-(-5x+10)=0
We get rid of parentheses
12x+5x-10+3=0
We add all the numbers together, and all the variables
17x-7=0
We move all terms containing x to the left, all other terms to the right
17x=7
x=7/17
x=7/17
| 5-c=6 | | -51(s+36)=17 | | 2.2x-1.9=22.3 | | Y=1/8x^2+2x-4 | | −4(m+6)=−8-4(m+6)=-8 | | -10+y+3=4y-130 | | -51(s+30)=17 | | 5.7*10^4p-3.6*10^6=4.2*10^6 | | 3/4+7/20=x | | 42/5+x=-32/11 | | 1/9x^2=-64/81x-7/81 | | 8|2-9p|-2=14 | | 4x+6+2×-3=9+5x-4 | | 5(y-2)+6=21- | | v+2-3(-4v-1)=5(v-1) | | 11x+17;x=-6 | | 13-7x;x=-10 | | -7-3j=-31 | | 9u-6+2(2u+5)=-5(u+2) | | 5(8+2x)=70 | | 4(x+4)=-3(5x-6)+x | | -x-12;x=4 | | 6(c+13)=12 | | 2x-38=82-4x | | 2(3-x)=11+(8-x) | | 0.5/2.3=n/16 | | (3x-1)/4=(2x+4)/5 | | 5x-32=x+24 | | 24-3;x=6 | | 137.7*6=x | | 2.1=h+4/3 | | -7(3x-7=-182 |